The Level of School Administrators' Communication Skills Predicting Teachers' Psychological Well-Being: An Examination in the Context of School Climate (Journal of Management and Educational Sciences, 2026)
The purpose of this study is to examine the relationships between school administrators' communication skills, school climate, and teachers' psychological well-being levels according to teachers' perceptions, and to determine the extent to which administrators' communication skills and school climate predict teachers' psychological well-being. The research was designed as a correlational survey model. The sample of the study consisted of 261 teachers working in vocational high schools in the Altındağ district of Ankara. The Communication Skills Scale, Psychological Well-Being Scale, and School Climate Scale were used as data collection tools. Descriptive statistics, independent samples t-test, one-way analysis of variance (ANOVA), Pearson's moment correlation analysis, and multiple linear regression analysis techniques were used in the analysis of the data. The research findings show that there is a positive and significant relationship between school administrators' communication skills and teachers' psychological well-being; however, there is a negative and significant relationship between perceptions of school climate and psychological well-being. According to the results of the multiple linear regression analysis, when administrators' communication skills and school climate are considered together, they significantly predict teachers' levels of psychological well-being. When examining the regression coefficients, it was determined that the strongest variable in predicting teachers' psychological well-being was administrators' communication skills. The results obtained reveal that managerial communication and the organizational context of the school play a critical role in enhancing teachers' psychological well-being.